Analisis Efektivitas Inflasi, Bi Rate, Nilai Tukar (KURS), Pembiayaan Murabahah, dan Pembiayaan Musyarakah Terhadap Profitabilitas Perbankan Syariah di Indonesia (Periode 2020 – Desember 2022) - Syaida Nur Pratiwi; Rusiadi Rusiadi; Annisa Ilmi Faried (AKUNTANSI 45, 2024)
This research uses secondary data where the variables used are Inflation, BI Rate, Exchange Rate (KURS), Murabahah Financing, Mudharabah Financing and Profitability (ROA) with a period of January 2020 – December 2022. This research aims to determine the contribution between variables and Which policy recommendations are good in the short, medium and long term. The analysis technique applied in this research is VAR, which is a technique that aims to determine short-term, medium-term and long-term impacts based on several historical variables. The data used is secondary data taken from BI and OJK and processed using the Eviews10 application. The dependent variable used in this research is Profitability (ROA), while the independent variables used are Inflation, BI Rate, Exchange Rate (Exchange Rate), Murabahah Financing, and Musyarakah Financing. The results of research based on VAR estimation results state that Profitability (ROA) is the largest contribution in influencing research variables.